2022
DOI: 10.3390/ijms23115894
|View full text |Cite
|
Sign up to set email alerts
|

The Common Cellular Events in the Neurodegenerative Diseases and the Associated Role of Endoplasmic Reticulum Stress

Abstract: Neurodegenerative diseases are inseparably linked with aging and increase as life expectancy extends. There are common dysfunctions in various cellular events shared among neurogenerative diseases, such as calcium dyshomeostasis, neuroinflammation, and age-associated decline in the autophagy-lysosome system. However, most of all, the prominent pathological feature of neurodegenerative diseases is the toxic buildup of misfolded protein aggregates and inclusion bodies accompanied by an impairment in proteostasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 304 publications
0
22
0
Order By: Relevance
“…However, data awareness in terms of pharmacological HD drug targets and potential agents is also crucial for novel drug discovery, design, and development. In fact, the target landscape with respect to HD is rich and diverse, which leaves much space for rational drug design approaches [ 2 , 14 , 15 , 17 , 20 , 21 , 22 , 27 , 35 , 79 ]. Many compounds with affinities to one or several of these targets have also been identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, data awareness in terms of pharmacological HD drug targets and potential agents is also crucial for novel drug discovery, design, and development. In fact, the target landscape with respect to HD is rich and diverse, which leaves much space for rational drug design approaches [ 2 , 14 , 15 , 17 , 20 , 21 , 22 , 27 , 35 , 79 ]. Many compounds with affinities to one or several of these targets have also been identified.…”
Section: Resultsmentioning
confidence: 99%
“…(v) Novel, diverse targets reducing muHTT production, enhancing muHTT degradation, and generally lowering muHTT-conferred (long-term) toxicity, and thus, positively affect HD onset and progression. These targets include CASPs [ 2 , 14 , 15 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 79 ], HSPs [ 2 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], HDACs [ 2 , 14 , 15 , 17 , 20 , 79 , 105 ], PDEs [ 14 , 15 , 17 , 31 , 35 , 36 ], and σRs [ 14 , 15 , 35 , 37 , 79 ], but also the adenosine 2A receptor (A2AR) [ 14 , 36 ], the AMP-activated protein kinase (AMPK) [ 20 , 31 , 79 ], the ERG-associated protein with SET domain (ESET) [ 106 , 107 , 108 ], the Kelch-like ECH-associated protein (KEAP) [ 31 , 56 , 109 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obvious possible candidates include neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, Huntington's disease, and Creutzfeld-Jacob disease. The role of intracellular Ca 2+ in general and of ER Ca 2+ in particular (Ureshino et al, 2019;da Costa et al, 2020;Lim et al, 2021;Callens et al, 2021;Kovacs et al, 2021;Guan et al, 2021;Huang et al, 2022;Ge et al, 2022;Kim et al, 2022) as well as of ER stress and accumulation of misfolded proteins (da Costa et al, 2020;Guan et al, 2021;Kim et al, 2022;Ren et al, 2021;Yasmeen et al, 2022;Shacham et al, 2019;Chakraborty et al, 2005) have indeed already been demonstrated in several neurodegenerative diseases.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…ER stress triggers an adaptive signalling reaction known as the unfolded protein response (UPR) and promotes quality control mechanisms [ 3 ]. The UPR is mediated via the activation of PKR-like ER kinase (PERK), inositol-requiring transmembrane kinase/endoribonuclease 1α (IRE1α), and activating transcription factor 6 (ATF6) pathways [ 10 ]. However, dysfunctioning and prolonged activation of UPR play an essential role in promoting pro-apoptotic events [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%